ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA SECTION BTS LINE PADA PT XYZ - Ridho Pratama, Ihsan; Sri Zetli (Computer Science and Industrial Engineering, 2025)
This study aims to analyze potential occupational health and safety (OHS) risks in the BTS Line section of PT XYZ using the Hazard and Operability Study (HAZOP) and Fault Tree Analysis (FTA) methods. Based on workplace accident data from 2021 to 2024, frequent incidents include finger pinching, hand scratches, foot injuries, and burns. The identification process revealed 10 work risk activities with varying levels, with 58.82% categorized as high risk and 5.88% as extreme risk. FTA analysis showed that the main causes of accidents stem from human error, improper use of personal protective equipment (PPE), and suboptimal equipment design. This research recommends risk control measures through engineering controls, administrative controls, and routine employee training. The implementation of these strategies is expected to reduce workplace accidents and create a safer and more productive working environment.